2011
DOI: 10.1080/09674845.2011.11730344
|View full text |Cite
|
Sign up to set email alerts
|

Predicting tumour response to anti-HER1 therapy using medical imaging: a literature review andin vitrostudy of [18F]-FDG incorporation by breast cancer cells responding to cetuximab

Abstract: Cetuximab, an anti-HER1 (EGFR) antibody, is currently under trial for the treatment of breast cancer. HER1 expression is not necessarily a predictor of response to cetuximab as mutant components of the pathways activated by HER1 which include PI3K/Akt can lead to resistance. Techniques that monitor events downstream of HER1 are more likely to provide an accurate measure of the efficacy of an anti-HER1 treatment. Glucose metabolism has been shown to be strongly influenced by the state of activation of PI3K/Akt.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Studies of patients with absent or low tumor EGFR expression by immunohistochemistry have found that response rates are statistically indistinguishable from those patients with higher EGFR expression, indicating that immunohistochemical staining may not always detect physiologically relevant receptor expression (2,3). An important consequence of EGFR activation is increased glucose uptake and retention, which supports tumor energetic and biosynthetic requirements (4,5,6), suggesting that 18 F-fluorodeoxyglucosepositron emission tomography (FDG-PET) may be a sensitive assay for detection of changes in EGFR activity (7,8). Here, we describe a chemotherapy-refractory patient whose tumor was negative for EGFR expression by immunohistochemistry in whom we used FDG-PET to show a panitumumab-mediated decrease in FDG accumulation over a period of 48 hours, leading to a progressive decline in metabolic activity and partial response by Response Evaluation Criteria in Solid Tumors (RECIST; ref.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of patients with absent or low tumor EGFR expression by immunohistochemistry have found that response rates are statistically indistinguishable from those patients with higher EGFR expression, indicating that immunohistochemical staining may not always detect physiologically relevant receptor expression (2,3). An important consequence of EGFR activation is increased glucose uptake and retention, which supports tumor energetic and biosynthetic requirements (4,5,6), suggesting that 18 F-fluorodeoxyglucosepositron emission tomography (FDG-PET) may be a sensitive assay for detection of changes in EGFR activity (7,8). Here, we describe a chemotherapy-refractory patient whose tumor was negative for EGFR expression by immunohistochemistry in whom we used FDG-PET to show a panitumumab-mediated decrease in FDG accumulation over a period of 48 hours, leading to a progressive decline in metabolic activity and partial response by Response Evaluation Criteria in Solid Tumors (RECIST; ref.…”
Section: Introductionmentioning
confidence: 99%
“…Using MTT (3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide) assays, cytotoxicity of DE and DAES with or without SO1861 (125 ng/mL) was determined on the EGFR-positive colon cancer cell line HCT 116 and the mammary gland carcinoma cell line MDA-MB-453, which expresses only low amounts of EGFR [ 25 , 26 ] (see also Additional file 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Here, HCT 116 cells were cultured in McCoy’s medium (Gibco, Thermo Fisher Scientific, Waltham, MA, USA). MDA-MB-453 cells (ATCC, Manassas, VA, USA) in contrast express low amounts of EGFR [ 25 , 26 ]. This cell line has been isolated from the metastatic site of a patient with mammary gland carcinoma [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, false-positive or equivocal results are a known limitation of FDG-PET/CT in cancer evaluation [41]. The metabolism of glucose is mediated by Akt (v-Akt murine thymoma viral oncogene)/PKB (protein kinase-B) pathway, and Akt is regulated by EGFR-PI3K (phosphatidylinositol-3-kinase) signaling [42]. Accordingly, it should not be assumed that FDG-PET/CT can be used for assaying the therapeutic response of all molecular-targeted therapies.…”
Section: Discussionmentioning
confidence: 99%